Concepções de criança e infância de professoras e professores indígenas : os desafios da educação intercultural - Pinho, Arlete Márcia de (2018)
e dissertation entitled "Conceptions of Children and Childhool of Indigenous Teachers and Teachers: The Challenge of Intercultural Education" is part of the research line Social Movements, Politics and Popular Education, in the sub-area Education and Indigenous Peoples, of the Master's course of the Graduate Program in Education of UFMT. The exploratory qualitative research systematizes data from interviews with 13 indigenous teachers of Bororo, Umutina, Paresi, Chiquitano and Nambikwara people in the process of continuous training in Cuiabá, united with the Project Action and Knowledge at School - UFMT, and two masters in education, indigenous leaders from Mato Grosso, one Bororo and one Bakairi. The interviews conducted in 2016 and 2017 aimed to understand the conceptions of childhood and children and how teachers seek to ensure their development by reference to the cultures of their specific ethnic groups, and with the two state authorities, to reflect the relations between the school and the education policy of each people. The research is linked to the studies and projects developed by the COEDUC / UFMT Research Group, and data was analyzed with reference to children and childhood in a contextualized way, taking into account the studies of culture, indigenous education and intercultural education. The main interlocutors of the study were Cuche (1999), Geertz (2008), Del Priore (2004), Ariès (1981), Heywood (2004), Sarmento and Gouvea (2009), Kuhlmann , Tassinari, Silva and Ferreira (2001), Tassinari, Grando and Albuquerque (2012), Luciano (2004), Corsaro (2011), Grando (2004, 2009, 2012), Nunes, Silva and Macedo (2017), Marin (2015) and Fleuri (2014). In conclusion conceptions of childhood express the sociocultural and historical construction of each indigenous people participating in this research, guiding traditional and school education aimed at inserting children and educating them based on the worldviews and perspectives of the future. In the current context of the dynamics with the interethnic and multicultural Brazilian society, indigenous school education, under the responsibility of the teachers that were interviewed, literacy and the guarantee of an intercultural education in the school are concerns in the dynamic ways of perceiving the child and the indigenous childhood.